Peran Perpustakaan Yayasan Mitra Netra Dalam Meningkatkan Minat Baca Bagi Penyandang Tunanetra - Nisrina Fitriyani; Azwar, Muhammad (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The purpose of this research is to find out about the role of the library in increasing reading interest for blind people. This research uses a qualitative approach with a case study method. Data collection through primary data obtained by in-depth interviews and observation, while secondary data obtained from documentation. Data validity techniques used were source triangulation, technique triangulation, and time triangulation. Determination of informants using purposive sampling method. The results showed that the role of librarians in increasing reading interest is as educators, managers, administrators, and supervisors. The role of librarians as educators is to provide a source of learning and entertainment references, narrate books, carry out User Education. The role of librarians as managers and administrators is to provide comfortable rooms, collect and manage accessible collections, provide reading support facilities, provide accessibility collection request services, prepare activity plans and annual budgets. While the role of librarians as supervisors is to collaborate with internal and external parties. In its role there are still obstacles faced by the library in order to increase interest in reading for blind people.